Photon flux density in a crop livestock forest system - Guimarães, Luanna Elis; Silva-Neto, Carlos de Melo; Calil, Francine Neves (Revista Ecologia e Nutrição Florestal - ENFLO, 2016)
This study was conducted in a crop livestock forest system in Cachoeira Dourada, Goiás state, Brazil. Aiming to contribute to a better understanding about plant-environment interaction, this study had as objective to analyze light input in two different periods (dry and wet season). For photon flux density (PFD) measurement, two quanta sensors (LI-250 A, Licor Inc., USA) were used, in photosynthetically active band. Data collection was done in each hour, starting at 9:45 and ending at 17:45, and also collected the control to full sun, and other collections in: (1 in the center of the row of trees, 2 – at 5 m of hedgerow 3 –at 10m of hedgerow 4- at 15m of hedgerow), in each point 4 replications were obtained. According to the observed results, it was possible to verify that there were differences among the chosen points, being the points 10 and 15 meters the ones that receive the most range of PAR.most receiving range (PAR). Therefore, CLFS system did not reduce photons flux density. Highest PFD was verified during the dry season however the highest variation was verified in the wet period. The greater the distance from the rows with trees, the greater the incidence of solar radiation.